1998
DOI: 10.1016/s0034-5288(98)90028-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of B and T lymphocytes and plasma cells in colonic mucosa from healthy dogs and from dogs with inflammatory bowel disease

Abstract: The aim of this study was to investigate the subpopulations of lymphocytes in the colonic mucosa of healthy dogs and dogs with inflammatory bowel disease (IBD). Fourteen normal dogs and 13 dogs with IBD were examined. Endoscopic biopsy specimens of colonic mucosa from each dog were stained specifically for pan T lymphocytes (CD3) and pan B lymphocytes (CD79a), and for plasma cells with methyl green pyronin (MGP) stain. Cells were counted by means of a grid and statistical analysis was performed on the data col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 39 publications
4
34
0
Order By: Relevance
“…Afterwards, the same researcher studied the large intestine of canines with IBD and noted an increase of IgA+ and IgG+ plasma cells and T cells (Jergens et al 1999b). Similar results were obtained by Stonehewer et al (1998) who described the percentage of plasma cells and T cells in the lamina propria. Healthy dogs had significantly lower numbers of T cells and B cells in the lamina propria and also also lower numbers of T cells in the grandular epithelium.…”
Section: Immunohistochemical Markerssupporting
confidence: 88%
“…Afterwards, the same researcher studied the large intestine of canines with IBD and noted an increase of IgA+ and IgG+ plasma cells and T cells (Jergens et al 1999b). Similar results were obtained by Stonehewer et al (1998) who described the percentage of plasma cells and T cells in the lamina propria. Healthy dogs had significantly lower numbers of T cells and B cells in the lamina propria and also also lower numbers of T cells in the grandular epithelium.…”
Section: Immunohistochemical Markerssupporting
confidence: 88%
“…The aetiopathogenesis of this chronic canine enteropathy, which can occur as an isolated clinical entity or concurrently with lymphocytic-plasmacytic enteritis (Jergens 1999), is poorly defined, although it is likely that immunologic, environmental, and genetic factors contribute (German et al 2003). Recent investigations into canine IBD have revealed changes in immune cell populations and inflammatory cytokine mRNA expression in both the small-and large-intestinal mucosa (Stonehewer et al 1998;German et al 2000German et al ,2001Ridyard et al 2002;Peters et al 2004), but the events leading up to these alterations remain poorly understood.…”
mentioning
confidence: 99%
“…In previous studies, CD3 + lymphocytes in the LE were specified by numbers of IEL per 100 enterocytes [7,14,16,17]. In contrast, counting the CD3 + cells per area using an image analyzing software program or a grid may prove to be easier to use in diagnostical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This inflammation is further classified by the type of cellular infiltrate (neutrophilic, eosinophilic, lymphocytic, plasmacytic and granulomatous), where lymphocytic-plasmacytic infiltration is the most common form in dogs [5]. Increased numbers of CD3 + lymphocytes in lamina propria (LP) and lamina epithelialis (LE) have been documented in lymphocytic colitis [6][7][8][9] in the duodenum of dogs with IBD [9,10], and in histiocytic ulcerative colitis [11]. In contrast to these studies, a reduced number of CD3 + cells were found in the small intestine of dogs with IBD [12].…”
Section: Introductionmentioning
confidence: 99%